Exploring HIV Self-Testing: Barriers and Facilitators among Undergraduate Students - Muendo, Nicholas; Thigiti, Joseph; Tembu, Osborn (International Journal of General Practice, 2024)
Introduction Globally, 36.7 million individuals live with HIV/AIDS, with 2.5 million new cases annually. Youth (14-25 years) account for 45% of these new infections. Those aged 15-24 years are less likely to be aware of their HIV status and engage in HIV care compared to older adults. This study explores the use of HIV self-testing to improve access to HIV care among Kenyatta University undergraduates. Objective To identify barriers and facilitators to HIV self-testing in this group. Methodology Employing multistage cluster sampling, 398 students were surveyed using a self-administered questionnaire. Results Of the participants (median age 21 years, 1:1.03 male-to-female ratio), 91.7% understood HIV's seriousness, with sexual intercourse as the primary transmission mode. Self-testing usage was 28.8%. Key barriers included fear of partner reaction, stigma, and lack of confidence. Significant facilitators were being female, knowledgeable about HIV, and sexually active. Conclusion Only 24% had prior HIV testing experience. The study highlights the importance of addressing fears and misconceptions while leveraging knowledge and sexual activity awareness to promote HIV self-testing.
Keywords: HIVST; UNDERGRADUATE; HIV